2010
DOI: 10.1136/gut.2009.195701
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an ASCL2 related stem cell signature and IGF2 in colorectal cancer liver metastases with 11p15.5 gain

Abstract: With unprecedented resolution a striking conservation of genomic alterations was demonstrated in liver metastases, suggesting that metastasis typically occurs after the pCRC has fully matured. In addition, we characterised a subset of liver metastases with an ASCL2-related stem-cell signature likely to affect metastatic behaviour of tumour cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 52 publications
5
85
3
1
Order By: Relevance
“…In 70 samples, PKLR mRNA was significantly upregulated in liver metastases relative to primary tumors ( Figure 3A). This upregulation was also observed in multiple independent data sets of unmatched ( Figure 3, B and C) and matched ( Figure 3, D and E) samples from patients with colorectal cancer (24)(25)(26)(27). These samples were from a total of 311 patients.…”
Section: Resultsmentioning
confidence: 74%
“…In 70 samples, PKLR mRNA was significantly upregulated in liver metastases relative to primary tumors ( Figure 3A). This upregulation was also observed in multiple independent data sets of unmatched ( Figure 3, B and C) and matched ( Figure 3, D and E) samples from patients with colorectal cancer (24)(25)(26)(27). These samples were from a total of 311 patients.…”
Section: Resultsmentioning
confidence: 74%
“…Most distant metastases genotypically and phenotypically resemble their primary tumor (11). This implicates that the changes enabling CTC to perform the necessary steps to cause distant metastases must be reversible and, thus, on a transcriptomic rather than a genomic level.…”
Section: Discussionmentioning
confidence: 99%
“…The dramatic phenotypic changes tumor cells need to undergo to become functional and tumorigenic CTC are no longer present in outgrown metastatic tumors and must therefore be reversible (9)(10)(11). This reversible phenotype is probably based on temporary differential regulation of metastasis-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…The combined results from such gain-and loss-of-function experiments indicate that Ascl2 controls the fate of intestinal stem cells (6). Several groups have demonstrated that Ascl2 is overexpressed in colorectal cancer (5,7,8). In addition, Ascl2 overexpression has the potential to shift the hierarchy of stem and progenitor cells within liver metastases, resulting in self-renewal rather than differentiation and potentially affecting the clinical behavior of these tumors (8).…”
mentioning
confidence: 99%